Exploring the impact of SNPs rs2476601, rs2488457, and rs33996649 on PTPN22 expression, structure, and anti-CCP level in rheumatoid arthritis of the Indian population: a case-control and computational study - Aswini, S.; Asha Devi, S. (Frontiers in Medicine, 2025)
BackgroundProtein Tyrosine Phosphatase Non-Receptor Type 22 (PTPN22) gene encodes for Lymphoid-Specific Tyrosine Phosphatase (LYP), predominantly expressed in T lymphocytes to regulate the immune responses by modulating T-cell proliferation and activation. Single Nucleotide Polymorphisms (SNPs) in PTPN22 alter the structure and function of LYP, leading to dysregulation of T-cell response and increasing the risk for autoimmune disease.MethodsTo investigate the intricate relationships between PTPN22 SNPs rs2476601, rs2488457, and rs33996649 and Rheumatoid Arthritis (RA) pathogenesis, genotyping was accomplished using High-Resolution Melting Analysis (HRMA) and Sanger sequencing in 229 RA and 239 control samples. The SNP rs2476601 disrupts the interaction between PTPN22 and Peptidyl arginine deiminase, which leads to an altered production of citrullinated proteins and consequently raises anti-CCP autoantibody levels. Hence, we further analyzed the impact of SNP rs2476601 on serum anti-CCP antibody levels in RA patients, and structural difference between the PTPN22 wild and R620W variant proteins by Molecular Dynamics Simulation (MDS). We also investigated the PTPN22 rs2488457 variant’s effect on PTPN22 mRNA expression level, noting its location in the gene’s promoter region, which may affect transcription and expression level. The influence of rs2488457 on PTPN22 mRNA expression level was determined by comparative threshold cycle method.ResultsThe statistical analysis confirms that RA samples with SNP rs2476601 C/T genotype (Odds Ratio (OR) = 3.6136; Confidence Interval (CI) = 2.2789 to 5.7300; p = 0.0001) and rs2488457 C/C genotype (OR = 1.5179; CI = 1.0453 to 2.2042; p = 0.0283) were associated with RA. SNP rs2476601 C/T genotype also elevated the serum anti-CCP antibody levels significantly (p = 0.01). The MDS result revealed significant structural and dynamic differences between wild and R620W variant forms of the PTPN22 protein. Furthermore, individuals with RA carrying the C/C genotype at the rs2488457 locus significantly (p = 0.0350) downregulated the PTPN22 mRNA expression level.ConclusionThis study suggests that PTPN22 SNPs rs2476601, rs2488457 are strongly linked with RA susceptibility in the Indian ethnicity.